A Study on Automotive Showrooms from the Viewpoint of Recommended Intention - Takumi Kato; Kazuhiko Tsuda (Maketingu Janaru, 2020)
One of the consumer behaviors created by the spread of electronic commerce (EC) is showrooming. This behavior refers to purchasing products cheaply on the Internet after checking the products in stores. This is a major threat to companies selling in-store products, and thus this subject is attracting attention from both industry and academia. However, the situation is significantly different in the automotive industry, where purchasing at a physical store is still mainstream. Therefore, the generic evaluation and discussion of the current situation in automotive showrooms is inadequate. In this study, the influence of the experience of visiting various types of showrooms, such as theme parks and cafes, on the recommendation intentions was evaluated in the Japanese automobile industry. According to the result of estimating the causal effect by propensity score based on the online survey, no significant effect was found. With respect to factors influencing the recommendation intention, the customers’ experience of the store is more important than the product. Politeness, affinity, and the customer’s sense of being made to feel special were extracted as factors contributing to the recommendation intentions. Although it is difficult to design a flow line directly to purchase behavior in an industry where EC conversion is not widespread, it is important to design consistent showrooms where customers can experience factors that influence their recommendation intention.